PERSONAL BRANDING BARBIE KUMALASARI UNTUK MERAIH POPULARITAS MELALUI INSTAGRAM - Rubiyanto Rubiyanto; Meisianita Fildyanti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
Kumalasari's personal branding efforts through instagram @barbiekumalasari often get harsh comment, bullying, and negative stigma from followers. In fact, it made her known and gained popularity. The purpose of this study was to analyze the Kumalasari personal brand through content on Instagram account @barbiekumalasari, as a form of personal branding to gain popularity. The author uses qualitative methods with an interpretive paradigm, and an intrinsic case study approach. The results showed that the uploaded content has met the ten guidelines for forming a personal brand, as a form of personal branding put forward by Keller, Parameswaran, and Jacob. Even though the content received positive and negative comments from followers, Kumalasari was able to gain popularity. In fact, she was given the title “Ratu Halu” because she identified herself with a Barbie doll as a form of strong personal brand. The personal brand that is attached to Kumalasari is a unique and different identity in the minds of followers, society, and media, which leads to the creation of popularity. In this study, the authors interpreted the new concept of Kumalasari as a 'Halu Barbie'